Analysis of the influence of macro and micro economic factors on stock investment risk (Study on cigarette companies listed in LQ-45) - Setia Budi Kurniawan; Diah Hermawan (University of Merdeka Malang, 2005)
This study aims to analyze the effect of gross domestic product growth rate, growth rate, inflation rate, deposit interest rate, rupiah exchange rate, dividend payment, asset growth, leverage, liquidity, earnings variability, and accounting beta on stock investment risk; and analyze which variables have a dominant influence on stock investment risk. The analysis technique used is multiple regression analysis. Based on the results of the study, shows that the variables of gross domestic product, inflation, deposit interest rates, exchange rates, dividend payment growth, leverage, liquidity, asset size, and earnings variability simultaneously have a significant effect on stock investment risk. Dividend payment variables, leverage, and asset size partially have a significant effect on stock investment risk, while the variables of gross domestic product, inflation, deposit rates, exchange rates, asset growth, liquidity, and income variability partially have no significant effect on stock investment. The variable that has the dominant effect on stock investment risk is leverage.